Tuberculous meningitis diagnosis and treatment: classic approaches and high-throughput pathways - Lin, Fangbo (Frontiers in Immunology, 2025)
Tuberculous meningitis (TBM), a severe form of non-purulent meningitis caused by Mycobacterium tuberculosis (Mtb), is the most critical extrapulmonary tuberculosis (TB) manifestation, with a 30–40% mortality rate despite available treatment. The absence of distinctive clinical symptoms and effective diagnostic tools complicates early detection. Recent advancements in nucleic acid detection, genomics, metabolomics, and proteomics have led to novel diagnostic approaches, improving sensitivity and specificity. This review focuses on nucleic acid-based methods, including Xpert Ultra, metagenomic next-generation sequencing (mNGS), and single-cell sequencing of whole brain Tissue, alongside the diagnostic potential of metabolomic and proteomic biomarkers. By evaluating the technical features, diagnostic accuracy, and clinical applicability, this review aims to inform the optimization of TBM diagnostic strategies and explores the integration and clinical translation of multi-omics technologies.